Genetic Regulation of Guanylate-Binding Proteins 2b and 5 during Leishmaniasis in Mice - Sohrabi, Yahya; Volkova, Valeryia; Kobets, Tatyana; Havelková, Helena; Krayem, Imtissal; Slapničková, Martina; Demant, Peter; Lipoldová, Marie (Frontiers in Immunology, 2018)
Interferon-induced GTPases [guanylate-binding proteins (GBPs)] play an important role in inflammasome activation and mediate innate resistance to many intracellular pathogens, but little is known about their role in leishmaniasis. We therefore studied expression of Gbp2b/Gbp1 and Gbp5 mRNA in skin, inguinal lymph nodes, spleen, and liver after Leishmania major infection and in uninfected controls. We used two different groups of related mouse strains: BALB/c, STS, and CcS-5, CcS-16, and CcS-20 that carry different combinations of BALB/c and STS genomes, and strains O20, C57BL/10 (B10) and B10.O20, OcB-9, and OcB-43 carrying different combinations of O20 and B10 genomes. The strains were classified on the basis of size and number of infection-induced skin lesions as highly susceptible (BALB/c, CcS-16), susceptible (B10.O20), intermediate (CcS-20), and resistant (STS, O20, B10, OcB-9, OcB-43). Some uninfected strains differed in expression of Gbp2b/Gbp1 and Gbp5, especially of Gbp2b/Gbp1 in skin. Uninfected BALB/c and STS did not differ in their expression, but in CcS-5, CcS-16, and CcS-20, which all carry BALB/c-derived Gbp gene-cluster, expression of Gbp2b/Gbp1 exceeds that of both parents. These data indicate trans-regulation of Gbps. Infection resulted in approximately 10× upregulation of Gbp2b/Gbp1 and Gbp5 mRNAs in organs of both susceptible and resistant strains, which was most pronounced in skin. CcS-20 expressed higher level of Gbp2b/Gbp1 than both parental strains in skin, whereas CcS-16 expressed higher level of Gbp2b/Gbp1 than both parental strains in skin and liver. This indicates a trans-regulation present in infected mice CcS-16 and CcS-20. Immunostaining of skin of five strains revealed in resistant and intermediate strains STS, CcS-5, O20, and CcS-20 tight co-localization of Gbp2b/Gbp1 protein with most L. major parasites, whereas in the highly susceptible strain, BALB/c most parasites did not associate with Gbp2b/Gbp1. In conclusion, expression of Gbp2b/Gbp1 and Gbp5 was increased even in organs of clinically asymptomatic resistant mice. It suggests a hidden inflammation, which might contribute to control of persisting parasites. This is supported by the co-localization of Gbpb2/Gbp1 protein and L. major parasites in skin of resistant and intermediate but not highly susceptible mice.